Processive movement by a kinesin heterodimer with an inactivating mutation in one head. - Thoresen, T.; Gelles, J. (Biochemistry, 2008)
A single molecule of the motor enzyme kinesin-1 keeps a tight grip on its microtubule track, making tens or hundreds of discrete, unidirectional 8 nm steps before dissociating. This high duty ratio processive movement is thought to require a mechanism in which alternating stepping of the two head domains of the kinesin dimer is driven by alternating, overlapped cycles of ATP hydrolysis by the two heads. The R210K point mutation in Drosophila kinesin heavy chain was reported to disrupt the ability of the enzyme active site to catalyze ATP P-O bond cleavage. We expressed R210K homodimers as well as isolated R210K heads and confirmed that both are essentially inactive. We then coexpressed tagged R210K subunits with untagged wild-type subunits and affinity purified R210K/wild-type heterodimers together with the inactive R210K homodimers. In contrast to the R210K head or homodimer, the heterodimer was a highly active (>50% of wild-type) microtubule-stimulated ATPase, and the heterodimer displayed high duty ratio processive movement in single-molecule motility experiments. Thus, dimerization of a subunit containing the inactivating mutation with a functional subunit can complement the mutation; this must occur either by lowering or by bypassing kinetic barriers in the ATPase or mechanical cycles of the mutant head. The observations provide support for kinesin-1 gating mechanisms in which one head stimulates the rate of essential processes in the other.